Core substitution of dihydrophenazine photoredox catalysts for organocatalyzed atom transfer radical polymerization - Puffer, Katherine, author; Miyake, Garret, advisor; Chen, Eugene, committee member; McNally, Andy, committee member; Peers, Graham, committee member (Colorado State University. Libraries, 2025)
Organocatalyzed atom transfer radical polymerization (O-ATRP) is a controlled radical polymerization method that uses organic photoredox catalysts (PCs) and visible light to produce polymers with well-defined structures. Organic PCs leverage an inherently sustainable resource, light, to drive chemical reactions under mild conditions and minimize dependency on rapidly depleting precious metals such as Ru and Ir, which are commonly used for catalysis. N,N-diaryl dihydrophenazine PCs in particular are notable for their success in mediating O-ATRP, producing polymers with low dispersities (Ð < 1.3). However, the non-unity initiator efficiency (I* < 100%) observed using dihydrophenazines in prior work shows their limited ability to achieve targeted molecular weights. This low I* has been attributed to a radical addition side reaction between the PC core and alkyl fragments generated during polymerization. In this work, core substitution (CS) is leveraged to modify PC structure as a route to block side reactivity and improve polymerization control. Exploration of alkyl CS revealed that the alkyl CS PC is the active catalyst during the majority of O-ATRP and can have improved catalytically relevant properties relative to the parent PC. Aryl and heteroatom CS PCs were also found to have improved PC properties, including longer excited state lifetimes and more highly reducing excited states. The new structure-property relationships revealed in this work were applied to improve polymerization outcomes and address current limitations of O-ATRP, such as expanding monomer scope and decreasing PC loadings. This work demonstrates the utility of CS as a versatile strategy to tune PC structure, properties, and performance while enhancing the ability of organic PCs to produce advanced polymeric materials.